Glossonema variens: A Threatened Food cum Medicinal Plant of Western Rajasthan (Indian Journal of Arid Horticulture, 2018)
Glossonema variens is threatened plant species in the lndian dese11 Due to overgrazing and destruction of habitat. its population is depicting in its natural habitats. It is being one of the important traditional foods cum medicinal planL'i for desert inhabitants in Thar Dc:sert India. This paper describes its c:thnic uses and potc:ntials nn
Keywords: Glossonema 11ariens, threatened; traditional food; conservation